Kerajaan Safawiyah dan Mughal: Jejak Sejarah, Politik dan Kontribusi dalam Peradaban Islam - Romadona Antika Wulandari; Kholid Mawardi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This article examines the history, political dynamics, and contributions of two great Islamic empires, namely the Safavids in Persia and the Mughals in India, in the 16th to 18th centuries AD. Through a library study approach, this study explores historical sources and academic literature to analyze the factors of glory and causes of decline of the two empires. The results of the study show that the Safavids and Mughals experienced a golden age in politics, economics, science, art, and religious tolerance. However, both experienced decline due to weak leadership, internal conflicts, and external pressure from foreign powers. This study shows that the progress of civilization is largely determined by the stability of government, visionary leadership, and the ability to adapt to the challenges of the times. This study provides an important reflection on the dynamics of the glory and decline of Islamic civilization which can be a mirror for the development of civilization in the modern era.